Epidrugs in precision medicine, the plausible way forward / Profesor Dr Ahmed Mahmoud Ahmed Alafify - Ahmed Alafify, Ahmed Mahmoud (Faculty of Pharmacy, 2023)
It is not only our genes that control how our bodies respond to drugs and cope with disease states, but also by identifying the modifications to our histone proteins that regulate gene expression, we can discover a whole new direction for diagnostic and therapeutic biomarkers and drug targets as well.In the last two decades, epidrugs have been developed to target the histone-modifying enzymes. It could be defined as small-molecular entities that inhibit epigenome and/or enzymes with epigenetic activity. Many preclinical evidence suggested that targeting epigenetic deregulation is an effective strategy to combat human diseases. However, implementing epidrugs in clinical practice is mainly limited to haematological malignancies.